Portrait of Child Labor in Small-Scale Oil Palm Plantations: Dillemma Between Education and Work. - Ghani, Mochammad Wahyu; Afriansyah, Anggi (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2023)
Amid increasing economic prospects and government support for oil palm plantations, oil palm plantations still have many social problems. The emergence of child labor in small-scale oil palm plantations (smallholders) is a fact. This article analyzes the dilemma related to the child laborers’ choice of working or continuing education in small-scale oil palm plantations in Seberu Village, Silat Hilir District, Kapuas Hulu District, West Kalimantan Province. We use an ethnographic approach to describe activities, behaviors, actions, conversations, and interpersonal interactions within social communities and small-scale farming family units. We found three main reasons why children consider education irrelevant to their daily needs and choose to work on small-scale oil palm plantations. The first factor is access, which is related to the distance to schools and inadequate road infrastructure. The second factor is the need for more imagination about the importance of going to school for the future. The third factor is lifestyle fulfillment rather than family economic difficulties.